ANALYSIS OF THE QUALITY OF INVESTMENT PASSPORTS OF PRECARPATHIAN LOCAL COMMUNITIES - Vasylchenko S.М.; Mykhailyshyn, L.I. (The actual problems of regional economy development, 2022)
The methods of analysis of the quality of investment passports of territorial communities and conducting of the analysis of the quality of investment passports of territorial communities of Precarpathian region has been proposed in the article. Marketing of the territory and marketing of investment opportunities of the community, as well as any marketing complex, should be carried out according to standard methods, as well as contain all the necessary set of community parameters that may interest potential investors and influence their investment decisions. Therefore, to analyze the quality of investment passports of territorial communities, the authors of the article developed their own methodology for assessing the quality of investment passports. The analysis of the quality of investment passports of territorial communities was carried out by monitoring those passports that are placed on the official websites of the territorial communities of Precarpathian region (62 territorial communities) and links to which can be found at https://decentralization.gov.ua/. However, if we didn't find a community investment passport while monitoring the site, we turned to the Google search engine to find such a document on other web resources. As evidenced by the review of the ratings conducted in the article, Precarpathian region today has a high investment potential, and a favorable investment climate has been created in the region, which allows to successfully attract investment for the development of the region's economy. But according to the authors of the article, such investment potential of Precarpathian region is not fully realized due to the little attention that territorial communities pay to the development of investment passports of communities. The authors of the article aimed to analyze the availability and quality of investment passports of communities of Ivano-Frankivsk region to identify reserves for further growth of investment activity in Precarpathian region. In addition, it is known that the investment passport is a key marketing tool of the territorial community, and in conditions of war, the investment passport of the community becomes the main reference point for businesses that relocate enterprises from the war zone. The results of the analysis showed that the final overall assessment of the quality of investment passports of communities in Ivano-Frankivsk region was low. The average score was 6.12 (on a 12-point scale), i.e. the quality of community investment passports is satisfactory. The main shortcomings of investment passports, which reduced their overall assessment, were non-compliance with the structure, lack of separate sections, or lack of information. In addition, according to the analysis, only 14 per cent of the region's communities have developed and placed investment passports on their websites.